International monetary reform : documents of the Committee of Twenty - International Monetary Fund; International Monetary Fund (Washington : nternational Monetary Fund, 1974)
This book gathers together the principal documents of the Committee of the Board of Governors of the International Monetary Fund on Reform of the International Monetary System and related issues. It was complied by the Committee of Twenty established in July 26, 1972.
Includes bibliographical references
usc 26/04/2018
Loans
Keywords: Foreign exchange; International finance; Balance of payments; Currency question; Special drawing rights